A high stability beam-scanning confocal optical microscope for low temperature operation. - Grazioso, F; Patton, B; Smith, J (2010)
We report on the design and performance of a high stability scanning confocal microscope for optical microscopy at low temperatures. By scanning the beam in a cold objective lens system, we achieve wide fields of view without compromising image quality. Photoluminescence from single nitrogen-vacancy centers in high purity diamond is used to illustrate the imaging and stability performance of the microscope.